2010
DOI: 10.4070/kcj.2010.40.9.423
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Ambulatory and Home Blood Pressure Monitoring

Abstract: Because blood pressure (BP) is an ever changing hemodynamic phenomenon, a BP value, once measured at a physician's office (Office BP), is often unrepresentative of an individual's true BP status. Both ambulatory blood pressure monitoring (ABPM) and home blood pressure monitoring (HBPM) provide more accurate and reproducible estimate of BP, and produce stronger predictive ability for cardiovascular outcome than conventional office BP. Two BP measuring techniques, ABPM and HBPM have been widely in clinical use f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Various features of the 24-hr pattern detected by ABPM have been assessed as potential triggers of target organ damage and cardiovascular (CV) events (3, 4). Particular attention has been paid to nocturnal BP variation, due to its association with poor CV prognosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…Various features of the 24-hr pattern detected by ABPM have been assessed as potential triggers of target organ damage and cardiovascular (CV) events (3, 4). Particular attention has been paid to nocturnal BP variation, due to its association with poor CV prognosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of studies have demonstrated that ABPM is more reproducible and a better predictor of organ damage and incidence of cardiovascular events compared with OBPM [3, 6]. In addition, ABPM identifies the white coat phenomenon (increased BP in a doctor’s office in patients with normal ambulatory BP) and discovers masked hypertension (normal doctor’s office BP in patients with high ambulatory BP [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ABPM identifies the white coat phenomenon (increased BP in a doctor’s office in patients with normal ambulatory BP) and discovers masked hypertension (normal doctor’s office BP in patients with high ambulatory BP [5-7]. ABPM also allows better control of BP in pregnant women with preeclampsia or eclampsia risk, subjects with diabetes and metabolic syndrome [3, 8-10]. ABPM is indicated in the clinical management of hypertensive patients with resistance to treatment (defined as BP above goal despite the use of three agents of different classes in optimal doses, including a diuretic) [2, 3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations